Insulin-like growth factor system components expressed at the conceptus-maternal interface during the establishment of equine pregnancy - Gibson, Charlotte; de Ruijter-Villani, M.; Stout, Tom A. E. (Frontiers in Veterinary Science, 2022)
In many species, the insulin-like growth factors (IGF1 and IGF2), their receptors and IGF binding proteins play important roles in preparing the endometrium for implantation, and regulating conceptus growth and development. To determine whether the IGF system may contribute to conceptus-maternal interaction during equine pre-implantation development, we evaluated mRNA expression for IGF system components in conceptuses, and endometrium recovered from pregnant and cycling mares, on days 7, 14, 21 and 28 after ovulation. We also investigated expression of IGF1, IGF2 and their receptors 6 and 11 days after transfer of day 8 embryos to synchronous (day 8) or asynchronous (day 3) recipient mares. Expression of IGF1 and IGF2, IGF1R, IGF2R, INSR and IGFBPs 1, 2, 4 and 5 was evident in endometrium and conceptus membranes during days 7-28. Endometrial IGF2, INSR, IGFBP1 and IGFBP2 expression increased between days 7 and 28 of pregnancy. In conceptus membranes, expression of all IGF system components increased with developmental stage. Immunohistochemistry revealed strong expression of IGF1, IGF2 and IGF1R in both endometrium and conceptus membranes, whereas INSR was highly expressed in endometrium but barely detectable in the conceptus. Finally, a negatively asynchronous uterine environment retarded IGF1, IGF2 and INSR expression in the conceptus, whereas in the endometrium only INSR expression was altered by asynchrony. The presence of IGFs, their receptors and IGFBPs in the endometrium and conceptus during early equine pregnancy, and down-regulation in the conceptus following asynchronous embryo transfer, suggest a role in conceptus-maternal communication during the preparation for implantation.